Realizing a regional network broadcasting system to promote competitiveness in local programming and fair broadcasting in Indonesia - Surokim (Plaridel, 2016)
Access online through this link: https://www.plarideljournal.org/article/realizing-regional-network-broadcasting-system-promote-competitiveness-local-programming-fair-broadcasting-indonesia